(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إن التطور السريع في مجالات كثيرة, لحل مشكلات عدد من المجتمعات والدول, له مضاعفات جانبية خطيرة على صحة الإنسان ووجوده, تمثلت هذه المضاعفات في وجود ظاهرة خطيرة هي الملوثات البيئية موضوع البحث الذي تمّ فيه تناول بعض من جوانب التلوث الناجمة عن مصفاة بانياس والتي تؤثر تأثيراً مباشر على صحة الإنسان ولقد وضِع الفرضين الآتيين لإثبات ذلك: الفرض الأول: إن الانبعاثات الغازية الناجمة عن بعض المنشآت لها أثر ذو دلالة إحصائية على صحة الإنسان. الفرض الثاني: إن الأصوات الصادرة عن بعض المنشآت لها أثر سلبي ذو دلالة إحصائية على حاسة السمع لدى السكان. ولقد تمّ الحصول على مجموعة من النتائج كان أهمها أن معظم أفراد العينة المنتقاة يشعرون بالتلوث بشكل مخيف ومزعج وأن غالبية الأفراد يعانون من أمراض عديدة أكثرها تنفسية وذلك بسبب تعرضهم للتلوث كذلك لوحظ أن الضجيج الموجود في المصفاة يؤثر على حاسة السمع لدى العمال وبناءً على هذه النتائج تمّ وضع مجموعة من التوصيات والمقترحات التي تساهم في حل مشكلة التلوث في المنطقة. The quick development in many domains to solve problems of various societies and countries has serious subsidiary consequences on human existence and health. These consequences are represented by the existence of a serious phenomenon, which is the environmental pollution, which forms our research object. We take into consideration some aspects of pollution, caused by Banyas refinery, which have a direct effect on human health. So, we put two assumptions, to prove it: The first assumption: gas emission resulted from some constructions has a statistically significant effect on human health. A second assumption: noise caused by some constructions has a significant statistically negative effect on hearing sense. We obtained some results of which, the most important one is that the majority of sampled individuals feel pollution in anxious and terrible way. So, most of individuals in the sample suffer from various diseases, especially respiratory diseases caused by their exposure to pollution.